The Influence of Servicescape on Revisit Intention Mediated by Perceived Service Quality (A Study on Cokelat Klasik Café in Malang) - Jaya, Qomarudin Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research tries to determine the influence of servicescape on revisit intention mediated by perceived service quality in Cokelat Klasik Cafe in Malang. This explanatory research explains causal relation between variables through hypothesis testing.Â Using purposive sampling technique, 300 consumers of Cokelat Klasik Cafe in Malang are selected as the sample. The sample should be at least 17 years of age and have visited Cokelat Klasik Cafe Malang at least once. The instrument of this research is assessed using validity test, reliability test, and classical assumption test, and the hypothesis is assessed using t test. The data of this study are analyzed using path analysis.The result of this study shows that servicescape significantly influences the revisit intention of Cokelat Klasik Cafe consumers in Malang, that servicescape significantly influences the perceived service quality of Cokelat Klasik Cafe consumers in Malang, that perceived service quality significantly influences the revisit intention ofÂ Cokelat Klasik Cafe consumers in Malang, and that perceived service quality mediates the influence of servicescape on the revisit intention of Cokelat Klasik Cafe consumers in Malang.Keywords: servicescape, perceived service quality, revisit intention